2023
DOI: 10.1002/mnfr.202200768
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effects and Macrophage Activation Induced by Bioavailable Cinnamon Polyphenols in Mice

Youngju Song,
Young Sung Jung,
Sunghyun Park
et al.

Abstract: ScopeCinnamon is a commonly used spice and herb that is rich in polyphenols. Due to the limited bioavailability of oral polyphenols, it remains unclear to which extent they can reach cells and exert a biological effect. This study aims to investigate the impact of bioavailable cinnamon polyphenols on lipopolysaccharide (LPS)‐stimulated macrophages.Methods and resultsA polyphenol fraction is prepared from cinnamon (Cinnamomi ramulus) (CRPF) by boiling cinnamon in water and adsorbing the extract onto a hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The main chemical component of cloves is clove volatile oil, which exhibits antioxidant, anti-inflammatory, antibacterial, and analgesic effects, while also promoting transdermal absorption [ 20 , 21 ]. Previous studies have shown that polyphenols in cinnamon can modulate macrophage anti-inflammatory phenotypes, and cinnamaldehyde (CA) can inhibit the expression of pro-inflammatory cytokines [ 22 , 23 ]. Furthermore, the essential oil of Cinnamomum species can reduce the levels of PGF 2α , Ca 2+ , and cyclooxygenase-2 (COX-2) in uterine tissues, thereby alleviating uterine smooth muscle spasms in a dysmenorrhea rat model [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main chemical component of cloves is clove volatile oil, which exhibits antioxidant, anti-inflammatory, antibacterial, and analgesic effects, while also promoting transdermal absorption [ 20 , 21 ]. Previous studies have shown that polyphenols in cinnamon can modulate macrophage anti-inflammatory phenotypes, and cinnamaldehyde (CA) can inhibit the expression of pro-inflammatory cytokines [ 22 , 23 ]. Furthermore, the essential oil of Cinnamomum species can reduce the levels of PGF 2α , Ca 2+ , and cyclooxygenase-2 (COX-2) in uterine tissues, thereby alleviating uterine smooth muscle spasms in a dysmenorrhea rat model [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of interferon (IFN) and the activation of toll-like receptors (TLRs) by bacterial lipopolysaccharides (LPS) cause M1 differentiation to begin, whereas IL-4 causes M2 polarization to begin [116]. Certain polyphenols from cinnamon are reported to activate macrophages and have an impact on lowering inflammation and enhancing immunological performance [117,118]. Reactive oxygen species (ROS) govern a wide range of complex biological activities, including angiogenesis, inflammation, differentiation, and proliferation.…”
Section: Polyphenols Modulate Macrophage Functions and Inflammationmentioning
confidence: 99%
“…M1 differentiation begins with the stimulation of interferon (IFN) by bacterial lipopolysaccharides (LPSs) and the activation of Toll-like receptors (TLRs), while M2 polarization is initiated by the release of interleukin-4 (IL-4) [ 235 ]. Evidence suggests that certain cinnamon polyphenols can activate macrophages, which in turn can reduce inflammation and enhance immunological performance [ 236 , 237 ]. An increasingly recognized field of research, immune-cell-mediated cancer therapy focuses on leveraging cytotoxic immune cells to combat cancer.…”
Section: Recent Studies and Emerging Trends On Polyphenolsmentioning
confidence: 99%